Levels of Zinc Application on the Agronomic Characteristics and Yield Performance of Lowland Rice - Baylon, Noel (JPAIR Multidisciplinary Research, 2019)
Since Rice is indispensable to almost all Filipinos as their primary food, it is necessary to aim for an additional greater harvest as an ultimate objective. The study was conducted to determine if there were significant differences in growth performance and on the yield of lowland rice applied with zinc sulfate at different levels. The experimental area was divided into four blocks for the number of replications and each block was further divided into 5 plots for the number of treatments adopting the Randomized Complete Block Design (RCBD). The following treatments were: T0-control-without application of zinc sulfate, T1-5kg of zinc sulfate, T2-10kg of zinc sulfate, T3-15kg of zinc sulfate, and T4 -20kg of zinc sulfate. Results showed significant differences in the plant height, the number of tillers, percentage of bearing culm, length of the panicle, percentage of filled and unfilled grains, grain yield per hill, grain yield per treatment, the weight of 1000 grains, except the number of grains per panicle. Maximum paddy yield was achieved in Treatment 4 (20kg zinc sulfate) and the minimum paddy yield was noted in treatment control (no zinc sulfate application). Zinc application increases the crop growth rate and yield of rice.